Aplicaciones clínicas de sistemas De indexación - Günther Sch. , Bruno; Vargas K, Victor (Revista Hospital Clínico Universidad de Chile, 1996)
CLINICAL APPLICATIONS OF INDEXATION SYSTEMS.The clinical applications of standarized physiological functions such as cardiovascular, respiratory and renal systems are discussed.